Molecular Identification of Blastocystis hominis Isolates in Patients with Autoimmune Diseases - Ahmed M. Mahmoud; Khadiga A. Ismail; Osama M. Khalifa; Maha M. Abdel-wahab; Howaida M. Hagag; Mahmoud K. Mahmoud (Applied Microbiology, 2023)
Background: Blastocystis hominis (B. hominis) is a ubiquitous parasite that has spread worldwide and is commonly present in human stool specimens. It was hypothesized that infection with B. hominis plays a role in the pathogenesis of autoimmune diseases in humans. The aim of this study is to test this hypothesis by investigating patients with autoimmune diseases. Patients with various types of autoimmune diseases with gastrointestinal symptoms were enrolled in this study as cases (n = 72) along with nongastrointestinal symptom patients as controls (n = 58). All participants in this study were subjected to history taking and were investigated for B. hominis infection via wet-mount microscopic stool examinations, staining with trichrome stain, and molecular-based tests applied to their fecal samples. Blood samples were also tested for complete blood counts. B. hominis were identified with specific PCR more in cases (12/72; 16.6%) than in controls (3/58; 5.2%), with a significant difference (p < 0.05). Significant decreases in white blood cell counts were demonstrated in systemic lupus erythematosus (SLE) and ulcerative colitis (UC) patients infected with B. hominis when compared to patients with nongastrointestinal symptoms (p-value < 0.05).